Prototype System Speed Detection dengan Sensor Infra Merah dan DHT11 berbasis Arduino Uno - Fauzan, Muhammad Raihan; Nurpulaela, Lela; Saragih, Yuliarman (Jurnal Ilmiah Wahana Pendidikan, 2024)
In 2019, it was recorded that traffic accidents in West Java Province reached 7.6 thousand with 3.3 thousand deaths occurring and it was also recorded that this continued to increase from 2015 to 2019 by around 10%. So I made this prototype to notify that if the vehicle speed has exceeded 50 km/hr then the LED will light up as a form of warning/notification that the vehicle has exceeded the specified speed limit, and if the vehicle does not exceed 50km/hr (<50km/hr) then The LED does not light up which indicates that the vehicle speed remains at the normal speed limit. In this research there are 4 stages, namely case study, system design, tool testing. data collection and discussion. The results of the test show that the infrared sensor can work well up to a distance of 20cm and detect no more than 35°. In testing the DHT11 sensor, it was found that the test results obtained a low % error with a fairly high % accuracy, so it can be concluded that the working system of this prototype can work well.